Mixed method review for integrating building information modeling and life-cycle assessments - Seyis, Senem (Building and environment, 2020)
Previous studies have suggested that building information modeling (BIM) and life-cycle assessments (LCAs) could be integrated to quantify and alleviate the environmental effects of buildings while simplifying and optimizing data acquisition. However, there has been no expert-based research into the true potential of BIM-based LCAs in a wider context with consideration of the advantages and disadvantages. This study aims to identify, classify, and prioritize these advantages and disadvantages using mixed methodological research and subject matter experts (SMEs). This includes a comprehensive literary review, semi-structured interviews with SMEs, and use of the Delphi method. A total of 21 advantages and 7 disadvantages associated with BIM-based LCAs were identified and classified. The advantages were grouped into four categories: decision making, material selection, sustainability performance, and waste reduction. The disadvantages were grouped into two categories: standardization and data processing. The Delphi method was applied via two rounds of questionnaires with ten SMEs to prioritize the advantages and disadvantages. The results of this study will provide practitioners and researchers with constructive information for the integrated use of BIM and LCAs and will create awareness in the architecture, engineering, and construction industry. The identified disadvantages show the requirements for future work and the priority rankings for both the advantages and disadvantages could be used by researchers and key stakeholders. •BIM-based LCAs could quantify and alleviate the environmental effects of buildings.•Pros and cons examined using mixed methodological research and subject matter experts.•Delphi method applied via two rounds of questionnaires with ten experts.•Priority rankings could be used by researchers/stakeholders to improve integration.•The identified disadvantages show the requirements for future work.